2022
DOI: 10.1029/2022je007186
|View full text |Cite
|
Sign up to set email alerts
|

A Revision of the Formation Conditions of the Vredefort Crater

Abstract: The Vredefort impact structure, located in South Africa and formed 2.02 Ga, is the largest confirmed remnant impact crater on Earth. The widely accepted impactor diameter and velocity to form this crater are 15 km and 15 km/s, respectively, which produce a crater diameter of 172 km. This is much smaller than the most commonly cited estimates (250–280 km), and while previous results were able to match the geologic evidence known at that time, these impact parameters are not consistent with more recent geologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 69 publications
3
22
0
Order By: Relevance
“…The Vredefort Dome experienced post‐impact temperatures that increase from the collar toward the center of the structure, with metamorphic conditions progressing inward from greenschist to granulite facies. They are interpreted to reflect a combination of the centripetally increasing effects of shock heating and uplift of progressively deeper crustal levels as a consequence of impact (Allen et al., 2022; Gibson, 2019; Gibson & Reimold, 2005; Ivanov, 2005). Numerical modeling (Allen et al., 2022; Ivanov, 2005) showed that the rocks increase in post‐shock temperature overprint radially inward from ~300°C in the collar rocks to >1000°C in the lithologies at the center of the dome, in good agreement with the shock petrographic findings of Gibson and Reimold (2005).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…The Vredefort Dome experienced post‐impact temperatures that increase from the collar toward the center of the structure, with metamorphic conditions progressing inward from greenschist to granulite facies. They are interpreted to reflect a combination of the centripetally increasing effects of shock heating and uplift of progressively deeper crustal levels as a consequence of impact (Allen et al., 2022; Gibson, 2019; Gibson & Reimold, 2005; Ivanov, 2005). Numerical modeling (Allen et al., 2022; Ivanov, 2005) showed that the rocks increase in post‐shock temperature overprint radially inward from ~300°C in the collar rocks to >1000°C in the lithologies at the center of the dome, in good agreement with the shock petrographic findings of Gibson and Reimold (2005).…”
Section: Geological Settingmentioning
confidence: 99%
“…They are interpreted to reflect a combination of the centripetally increasing effects of shock heating and uplift of progressively deeper crustal levels as a consequence of impact (Allen et al, 2022;Gibson, 2019;Gibson & Reimold, 2005;Ivanov, 2005). Numerical modeling (Allen et al, 2022;Ivanov, 2005) showed that the rocks increase in post-shock temperature overprint radially inward from ~300°C in the collar rocks to >1000°C in the lithologies at the center of the dome, in good agreement with the shock petrographic findings of Gibson and Reimold (2005). Beaton et al (2022) recently provided a detailed analysis of metamorphic overprints in the collar of the Vredefort Dome and concluded that the regional Ventersdorp volcanism on the central Kaapvaal craton at about 2.7 Ga was likely responsible for lower amphibolite to upper greenschist facies metamorphism that affected the collar strata prior to the impact event.…”
Section: Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The formation of Vredefort has been modeled with shock physics code SALEB by Ivanov (2005), and iSALE by Allen et al. (2022). The latter work reports the most updated simulations for the Vredefort impact and have been shown to match a number of observational constraints, particularly the spatial distribution of shock features.…”
Section: Introductionmentioning
confidence: 99%